Implementation of ANN with the Cyclical Order Method For Forecasting the Life Span of the World’s Population - Muhammad Rizal; Elviawaty Muisa Zamzami (IJISTECH (International Journal of Information System and Technology), 2019)
This study aims to predict the age (life expectancy) of the world's population. This research is the development of research that has been done before. But in this study only to get the best architectural model to predict the age (life expectancy) of the world's population, using the Cyclical Order method. Whereas in this follow-up research, it will produce forecasting in the form of age (life expectancy) of the population in the world based on a model that has been obtained from previous research. The research data is the age data (life expectancy) of the world's population from the United Nations: "World Population Prospect: The 2010 Revision Population Database". This study uses 5 architectural models including: 3-5-1, 3-8-1, 3-10-1, 3-5-8-1 and 3-5-10-1. Of the 5 models used, architectural models 3-5-10-1 are the best with an accuracy of 97%, the value of MSE training is 0,0009979400 and MSE testing is 0,0008358919. Forecasting results from this study are expected to be a reference for governments in the world, especially Indonesia to pay more attention to the level of health and well-being of its population so that the level of life of the population is getting better and higher.